Specific stretchers enhance rapid extraction by tactical medical support teams in mass casualty incidents. Issue 2 (February 2019) - Service Medical du Raid; Reuter, Paul-Georges; Baker, Chloe; Loeb, Thomas
Highlights: There are different types of extraction method, which are not equivalent. Based on the context, an appropriate evacuation method should be considered. Evacuation without devices is the fastest method, but not the safest, nor the most "stabilising". The "flexible tarp" method could be a good compromise between speed and stability. Abstract: Objective: In mass casualty incidents where the threat is on-going, victim evacuation remains a challenge: fast extraction while respecting spinal immobilisation and haemorrhage control. Different devices can be used but their suitability has not been compared. Methods: We conducted a simulation study comparing eight extraction devices with a randomisation of the order of testing. Five teams, consisting of four officers, evacuated a single victim in five steps: device's deployment, loading the victim, carrying the victim along a corridor, negotiating a corner passage and a descent by staircase. Primary outcome was the emergency extraction time, from deployment to the first obstacle. Secondary outcomes included ease of transport and victim's stability, rated from 1 (worst) to 10 (best). Results: One hundred and sixty simulations were carried out. The median emergency extraction time was 16.7 [IQR: 11.6–24.9] seconds. The three speediest devices were the "firefighters' worn", "snogg" and "flexible tarp", taking 9.7 [8.1–11.0], 11.7 [10.9–15.4] and 12.2 [11.2–17.9] seconds respectively (p < 0.0001). Regarding the ease of transport, the three best-evaluated devices were the "firefighters' worn", "strap" and "flexible tarp" with 10 [9–10], 9 [8–9] and 8 [8–9] respectively (p < 0.0001). Considering stability reported by simulated victims, the three best-evaluated devices were the "inflated stretcher", "flexible tarp" and "firefighters' worn" with 8.0 [7.8–9.0], 8.0[7.0–8.0] and 6.5 [6.0–7.0] respectively. Conclusion: Devices were not equivalent in terms of extraction time and suitability criteria. For rapid extraction of victims from danger zones, the "firefighter's worn" and "flexible tarp", as very simple stretchers, seem to be the most appropriate devices.